Improving prenatal diagnosis with combined karyotyping, CNV-seq and QF-PCR: a comprehensive analysis of chromosomal abnormalities in high-risk pregnancies - Liu, Jia-pei; Wang, Shan-Bing; Luo, Li; Guo, Ya-mei (Frontiers in Genetics, 2025)
ObjectiveThis study aims to assess the diagnostic efficacy of a combined approach integrating chromosomal karyotyping, copy number variation sequencing (CNV-seq), and quantitative fluorescence polymerase chain reaction (QF-PCR) in detecting chromosomal abnormalities in high-risk pregnancies.MethodsThis retrospective study analyzed 617 high-risk pregnancies undergoing prenatal diagnosis from February 2023 to August 2024, with amniotic fluid samples concurrently analyzed using karyotyping, CNV-seq, and QF-PCR. We evaluated clinical characteristics, diagnostic yields, and inter-method concordance rates. Longitudinal follow-up assessed pregnancy outcomes and neonatal phenotypes, with particular emphasis on cases demonstrating diagnostic discrepancies or variants of uncertain clinical significance.ResultsThe integrated approach detected chromosomal abnormalities in 12.5% (77/617) of cases, significantly higher than the rates achieved by karyotyping alone (9.7%) and CNV-seq/QF-PCR alone (8.3%) (p < 0.05). Karyotyping showed full concordance with CNV-seq and QF-PCR in detecting major chromosomal aneuploidies, identifying 21 cases of trisomy 21 and 4 cases of trisomy 18. CNV-seq uniquely identified additional pathogenic copy number variations in 2.1% of cases and variants of uncertain significance (VUS) in 3.2% of cases, both undetectable by conventional karyotyping. Subjects with high-risk non-invasive prenatal testing (NIPT) results had the highest abnormality detection rate (57.6%, p < 0.05). Follow-up data revealed pregnancy termination in 44 of 97 cases with chromosomal abnormalities. Notably, neonates carrying pathogenic CNVs inherited from asymptomatic parents demonstrated normal phenotypes.ConclusionThe integration of karyotyping, CNV-seq, and QF-PCR provides superior diagnostic yield compared to individual testing strategies in high-risk pregnancies. Although karyotyping remains the gold standard for detecting major chromosomal aberrations, CNV-seq and QF-PCR enhance diagnostic precision through detection of submicroscopic variations. Multi-center studies with larger cohorts are needed to confirm these findings and clarify the clinical significance of uncertain variants.